The Lack of Association Between Bacille Calmette-Guerin Vaccination and Clustering of Aboriginals with Tuberculosis in Western Canada - Victoria J Cook; Eduardo Hernández-Garduño; Dennis Kunimoto; Earl S Hershfield; E Anne Fanning; Vernon H Hoeppner; R Kevin Elwood; J Mark FitzGerald; Canadian Molecular Epidemiology of Tuberculosis Study Group (Canadian Respiratory Journal)
BACKGROUND: Tuberculosis (TB) remains a major health problem for Aboriginal people in Canada, with high rates of clustering of active TB cases. Bacille Calmette-Guérin (BCG) vaccination has been used as a preventive measure against TB in this high-risk population.